Sex-related differences in extracranial complications in patients with traumatic brain injury - Brandi, Giovanna; Gambon-Mair, Alma; Berther, Lara Selina; Bögli, Stefan Yu; Unseld, Simone (Frontiers in Neurology, 2023)
Background: Extracranial complications after traumatic brain injury (TBI) occur often. Their influence on outcome is uncertain. Furthermore, the role of gender on the development of extracranial complications following TBI remains poorly investigated. We aimed to investigate the incidence of extracranial complications after TBI with particular focus on gender-related differences with regard to complications and their influence on outcome. Methods: This retrospective, observational study was conducted in a level I university swiss trauma center. Consecutive patients with TBI admitted to the intensive care unit (ICU) between 2018 and 2021 were included. Patients' and trauma characteristics, provided surgical and medical care, in-hospital complications (i.e., cardiovascular, respiratory, renal, metabolic, gastrointestinal, hematological, and infectious) as well as functional outcome 3 months after discharge were analyzed. Data was dichotomized by gender or by outcome. Univariate as well as multivariate logistic regression was performed to reveal possible associations between gender, outcome and complications. Results: Overall, 608 patients were included (male n=447, 73.5%). Extracranial complications occurred most frequently in cardiovascular, renal, hematological and infectious systems. Men and women suffered similarly from extracranial complications. While men needed correction of coagulopathies more often than women (p=0.029), women suffered more frequently from urogenital infections than men (p=0.001). Similar results were found in a subgroup of patients (n=193) with isolated TBI. A multivariate analysis did not show extracranial complications to be independent predictors of unfavorable outcome. Conclusions: Extracranial complications following TBI occur frequently during the ICU-stay, affect almost all organ systems but are not independent predictors of unfavorable outcome. The results suggests that gender- specific strategies might not be needed for the treatment of extracranial complications in patients with TBI.